2004
DOI: 10.14411/eje.2004.033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parasitoid associated factors of the endoparasitoid Glyptapanteles liparidis (Hymenoptera: Braconidae)

Abstract: Abstract. The endoparasitoid Glyptapanteles liparidis (Hymenoptera: Braconidae) injects polydnavirus and venom together with eggs into its Lymantria dispar (Lepidoptera: Lymantriidae) host larvae during oviposition. We studied effects of these parasitoid associated factors by means of γ-irradiation-induced pseudoparasitization. The application of radiation for sterilization of female wasps as a tool to study interactions between parasitoid associated factors and the host is demonstrated in this paper. When was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
(26 reference statements)
2
17
1
Order By: Relevance
“…PDV/venom prevented the fatal immune response. Previous work had already shown that pseudoparasitized L. dispar larvae show reduced encapsulation of implanted artificial objects and reduced hemolymph melanization (Tillinger et al 2004). However, as is suggested by our findings from the dissections, G. liparidis larvae implanted without teratocytes still suffered some attack from the host immune system and were apparently unable to complete their development.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…PDV/venom prevented the fatal immune response. Previous work had already shown that pseudoparasitized L. dispar larvae show reduced encapsulation of implanted artificial objects and reduced hemolymph melanization (Tillinger et al 2004). However, as is suggested by our findings from the dissections, G. liparidis larvae implanted without teratocytes still suffered some attack from the host immune system and were apparently unable to complete their development.…”
Section: Discussionsupporting
confidence: 59%
“…Glyptapanteles liparidis females were g-irradiated based on the method outlined in Tillinger et al (2004). Six-day-old female wasps with at least one oviposition experience were placed in ventilated 10 )10 )15-cm plastic boxes and irradiated with 96 Gy (at a dose rate of 25.6 Gy/min) in a Gammacell 220 cobalt-60 irradiator (Atomic Energy of Canada Ltd.) at the FAO/IAEA Agriculture and Biotechnology Laboratories, Seibersdorf, Austria.…”
Section: Irradiation Of Parasitoid Waspsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-parasitized and X-ray-parasitized larvae pass through six larval instars, but the latter become developmentally arrested in the prepupal stage, as do larvae developing from eggs injected with CiV/ venom (Soller & Lanzrein, 1996). X-ray irradiation of wasps (24-96 Gy) has recently also been used in another parasitoid-host system to study the role of the associated bracovirus (Tillinger et al, 2004).…”
Section: Methodsmentioning
confidence: 99%